Efecto de la aplicación de fertilizantes completos tipo prill sobre la producción de arroz (Oryza sativa L.) bajo riego en la zona de Babahoyo - Zambrano Carriel, Yuri Berardo (2020)
The experimental work was carried out on the grounds of the "Macondo 2" farm owned by Abg. Ausberto Colina Gonzalvo, in Babahoyo canton, the rice variety used was SFL-11, in which the effect of the application of complete prill-type fertilizers on the production of irrigated rice was determined. With this, the effects of the doses of the products on the agronomic behavior and an economic analysis of the grain yield based on the cost of the treatments were evaluated. The randomized complete blocks experimental design was used, with 11 treatments and three repetitions. Variables were evaluated: plant height, number of tillers, number of panicles, length of panicles, number of grains per panicle, weight of 100 grains, days to flowering, days to harvest, grain yield, partial productivity per nutrient and analysis economic. The evaluated variables were exposed to the analysis of variance, and the Tukey test was applied at 5 % significance to determine the statistical difference between the means of the treatments. Observing the experimental results, it was found that there was variability in the growth of the plants treated with the various sources. In addition, there was a greater number of tillers per square meter with the prill sources. While the number of panicles was found with Hydran 300 kg ha-1 + Rafos 300 kg ha-1. It was not possible to find statistical significance in the variables days to flowering, days to harvest and panicle length. A greater number of grains and grain weight was obtained by applying Hydran 300 kg ha-1 + Rafos 300 kg ha-1, as well as a higher yield (6633.52 kg ha-1). Higher PPN values were high for N-P-K relative to the untreated control.